Avaliação da política de cashback do Programa Nota Fortaleza, uma análise empírica para os anos de 2013 a 2019 - Costa, Raniere Fontenele de Azevedo (2020)
In view of the scenario of seeking alternatives for the balance between income and expenses, the action of increasing the tax due is an option prior to the increase in the tax burden. In this way, the evaluation of the effectiveness of the Nota Fortaleza Program, through an empirical analysis of the return policy of part of the ISSQN (cashback), serves to gauge effective impact for society. The evaluation also verifies two other aspects of service providers: socioeconomic aspect, through the Human Development Index (HDI) of the neighborhood where the establishment is located and tax aspect, by the option for the Simples Nacional regime. The assessment of the aforementioned aspects occurred in isolation, jointly and with effects not orthogonal to each other. Panel data, of the tax posted by electronic invoice, issued to natural persons, regardless of participation in the Nota Fortaleza Program, consolidated by service companies in the Municipality of Fortaleza, by exercise and competence, were used. For that, the difference in differences or diff-in-diff model was used. The results showed that the Program brought significant impacts, greater among those not opting for Simples Nacional and located in high HDI neighborhoods. In addition, there was an increase, with the assumptions adopted, in terms of actual tax values, becoming an effective tax instrument.